Book Reviews (The Muslim world, 1951)
Muslim Institutions. By Maurice Gaudefroy-Demombynes, translated from the French by John P. MacGregor. London, George Allen and Unwin, Ltd. pp. 216. USD3.50. Etudes orientales a la memoire de Paul Hirschler. Éditeés par O. Komlós. Budapest, 1950. pp. vi, 144, 12. Le Coran. Traduction par O. Pesle et Ahmed Tidjani. 2e édition. Paris, Éditions Larose, 1948. pp. xvi, 458. Trekking Among Moroccan Tribes. By James Haldane. London, Pickering and Inglis, Ltd., 1948. pp. 198 and 13 illustrations. 15/ Desert Calling. By Anne Fremantle. New York, Henry Holt and Company, 1949. pp. ix, 364. USD4.00. The Sanusi of Cyrenaica. By E. E. Evans-Pritchard. Oxford, Clarendon Press, 1949. pp. viii, 240. American price USD6.50. Islamic Society and the West: A Study of the Impact of Western Civilization on Moslem Culture in the Near East. By H. A. R. Gibb and Harold Bowen. Volume I, Islamic Society in the Eighteenth Century, Part I. London and New York, Oxford University Press (Issued under the auspices of the Royal Institute of International Affairs), 1950. pp. xi, 386. USD4.50. The Struggle for Palestine. By J. C. Hurewitz. New York, W. W. Norton and Company, 1950. pp. 404. Tales From The Arab Tribes. By C. G. Campbell. New York, Macmillan, 1951. pp. 252. USD2.50. Afghanistan: A Study of Political Developments in Central Asia. By W. K. Fraser- Tytler. New York, Oxford University Press, 1950. pp. 330. USD5.00. Pakistan, The Fatherland of the Pak Nation. (Pakasia Liternture Series No. 1) By Choudhary Rahmat Ali. Third Edition. Cambridge, The Pakistan National Liberation Movement, 1947. pp. 376. The Population of India and Pakistan. By Kingsley Davis. Princeton, N. J., Princeton University Press, 1951. pp. 263. USD7.50. The Malays, A Cultural History. By Sir Richard Winstedt. New York, The Phil- osophical Library, Inc., 1950. pp. 190. Kahlil Gibran. A Biography. By Mikhail Naimy. With a preface by Martin L. Wolf. New York, Philosophical Library, 1950. pp. 267. USD3.75. A Treasury of Kahlil Gibran. Edited by Martin L. Wolf; Translated from the Arabic by Anthony Rizcallah Ferris. New York, Citadel Press, 1951. pp. 417. USD3.95. The Metaphysics of Rumi. Bv Dr. Khalifa Abdul Hakim. Lahore. Shaikh Muhammad Ashraf, 1949. pp. vii,'183. Rs. 3/12. Rumi, Poet and Mystic, 1207-1273. Edited by Reynold A. Nicholson. London, George Allen and Unwin, Ltd., 1950, pp. 190, USD2.00. Openbaring en Rede in de Islamietische Filosofie van al-Farabi tot Ibn Rushd. By D. C. Mulder. Amsterdam, Vrije Universiteit, 1949. pp. 184.